Knowledge and attitudes of radiation therapists and undergraduate students towards older people. Issue 3 (August 2015) - O'Donovan, A.; O'Herlihy, A.; Cunningham, M.
Abstract Purpose Rapidly changing demographics worldwide mean that there will be a significant increase in the number of older cancer patients requiring radiation therapy treatment in the coming decades. Education is regarded as a key factor in addressing attitudes towards older people among healthcare professionals and has been proven to influence the quality of care received. To our knowledge, there is only one previous study specifically in relation to radiation therapists (RTs), and this included a small sample of RTs. The aim of this study was to investigate the knowledge and attitudes of RTs and RT students towards older people. Methods A cross-sectional survey design was used, consisting of: 1) demographics, 2) knowledge and 3) attitudes. Knowledge was assessed using the Facts of Aging Quiz (FAQ), while Kogan's Attitude towards Old People (KAOP) Scale was used to assess attitudes. The study population included radiation therapists (RTs) working in Ireland and undergraduate students. Results Mean knowledge scores in this study were recorded as 11.82 (SD = 3.07)for RTs and 12.17 (SD = 2.55) for students out of a possible 24, i.e. 49% and 51%, respectively. Average attitude scores were documented as 126.12 (SD = 10.06) for RTs and 125.30 (SD = 10.28) for RT students, out of a possible 170 i.e. 74% for both qualified RTs and students. There were no significant differences between students and qualified RTs in relation to both knowledge and attitude scores. Only 44% of RTs stated that their undergraduate degree equipped them with the necessary skills to deal effectively with older patients. Conclusion RTs have a prominent role in the provision of care to cancer patients, the majority of whom are aged 65 and older. Provision of optimal care to older people undergoing radiotherapy will require "age attuning" of the profession, both at undergraduate and postgraduate level. The findings of this research indicate that RTs and RT students have average knowledge and very positive attitudes towards older people.